(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The extensive inquiries of the Blast domination number, this article dissects upsetting the parameter over Jump graph. The theoretical properties of the Blast domination number of a jump graph plus its accurate values for some customary graphs are derived. Relations between the Blast domination number of a jump graph and the Blast domination number of the analogous graphs are additionally perceived